Faktor-Faktor Yang Berhubungan Dengan Kejadian Tuberkulosis Paru Di Puskesmas Limboto - Ririn Pakaya (Universitas Widya Gama Mahakam Samarinda, 2020)
Background: Based on Indonesian Basic Health Research Data 2018 showed that Pulmonary Tuberculosis (TB) incidence in Indonesia 2013-2018 are 0,4%, whereas in Gorontalo district on last 3 years who has Pulmonary Tuberculosis with prevalence 626 cases. Objectives: The research aims at investigating the factors related with Pulmonary Tuberculosis incidence in Puskesmas Limboto 2018. Research Metodes: This research used observational analytic with cross sectional study. The populations of this research are all patients pulmonary tuberculosis and suspect of Pulmonary Tuberculosis 478 respondents, with total of samples are 220 respondents. The techniques of collecting samples used purposive random sampling. Results: The findings reveal that Fisher exact value 0,000 < ɑ=0,05 which means there is a relation between age with Pulmonary Tuberculosis incidence. X2 count value 0,000 < ɑ=0,05 which means there is a relation between education with Pulmonary Tuberculosis incidence. X2 count value 0,000 < ɑ=0,05 which means there is a relation between economy status with Pulmonary Tuberculosis incidence. X2 count p value 0,000 < ɑ=0,05 which means there is a relation between smoke habit with Pulmonary Tuberculosis incidence. X2 count p value 0,000 < ɑ=0,05 which means there is a relation between home contact with Pulmonary Tuberculosis incidence. Conclusion: There are relationships between age, education, economic status, smoking and home contact with the incidence of pulmonary Tuberculosis in Public Health Center of Limboto in Limboto subdistric Gorontalo District in 2018. Keywords: Pulmonary Tuberculosis, Age, Education, Economy Status, Smoke and Home Contact.